Marie-Antoinette Alamenciak, Revoir la théorie littéraire par le Moyen Âge. Le personnage dans les Quinze joies de mariage, les Cent Nouvelles nouvelles, les Arrêts d’Amour de Martial d’Auvergne (xive-xve siècles) - Marie-Antoinette Alamenciak (Perspectives Médiévales)
This thesis aims to question the current state of literary theory concerning the character, using three collections from the late Middle Ages : Quinze joies de mariage, Cent Nouvelles nouvelles, Arrêts d’Amour. When medieval literature is taken into account by literary theory, its characters are reduced to types. The aim is therefore to examine the theoretical and critical genealogy that has produced the valorization of a certain character – from the nineteenth-century novel – which has led to negative judgments of medieval characters, particularly those in our corpus. After stripping the type of its modern negative prejudices, we study the consequences of a predominantly generic approach to the corpus. We show that fiction – possible worlds, transfictionality – provides an objective and rich understanding of our characters. The second part deconstructs preconceived ideas about the writing of the type, seen as inconsistent. An analysis of nouns and adjectives through a gender-based approach challenges these supposed shortcomings, which leads us to question the social status of clothing. The third part looks at the question of reception from three angles – rhetoric, printed editions, narrative recycling – leading to an examination of the cognitive act of reading, which is aesthetic, emotional and social. Through this work, we hope to provide some guidelines for a more in-depth study of characters portrayed in short texts, from any literary genre and period.